Strengthening discipline in state schools: constructions of discipline in a public policy moment. Issue 3 (4th May 2018) - Carden, Clarissa
ABSTRACT: This article uses critical discourse analysis to interrogate government documents associated with the passing of the Education (Strengthening Discipline in State Schools) Act 2013 in Queensland, Australia. It uses these documents to demonstrate the way in which the discourse of discipline has been constructed in order to legitimate the removal of legislative safeguards intended to curtail the disciplinary power of school officials.